Virulence profile of Escherichia coli O157 strains isolated from surface water in cattle breeding areas - Tanaro, J D (2018)
Fil: Tanaro, J D. Cátedra de Microbiología, Facultad De Bromatología, Universidad Nacional de Entre Ríos, Gualeguaychú; Argentina.